Village Fund Management in Capital Participation of Village Owned Business in DPMPK, West Kutai Regency - Aliansyah Aliansyah; Musmuliadi Musmuliadi; Agustinus Djiu (International Journal of Social Service and Research, 2022)
This study aims to determine the management of the Village Revenue and Expenditure Budget (APBDes) in the Village / Village of West Kutai Regency and analyze the accountability of the village government in managing the Village Revenue and Expenditure Budget (APBDes). This research was started from April 2022 to June 2022 with the research location at the Office of Community and Village Empowerment (DPMK) West Kutai Regency. This research is a qualitative research with the type of descriptive research. The technique of collecting data is by using interview, observation, and documentation techniques. While the research instruments are the researchers themselves, interview guides, and communication and documentation tools. The data analysis of this research used an interactive model, namely data reduction, data presentation, and data verification of conclusions. Based on the results of research that has been carried out on all the data obtained, it is concluded that accountability and transparency affect the management of village funds. while participation does not significantly affect the management of village funds. Meanwhile, accountability, transparency and participation simultaneously affect the management of village funds in West Kutai Regency.Village Owned Enterprises are good, but not yet fully maximized in encouraging the level of community welfare in West Kutai Regency. This is because there are several business units that are already good and capable in improving the quality of the community, but there are several business units that have not provided the benefits as they should as a forum in achieving the goals of BUMK itself.